2006
DOI: 10.1042/bj20060444
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of human angiotensinogen: insights into its structural mechanism and functional significance

Abstract: In the present study, we have investigated the in vitro polymerization of human plasma AGT (angiotensinogen), a non-inhibitory member of the serpin (SERine Protease INhibitor) family. Polymerization of AGT is thought to contribute to a high molecular mass form of the protein in plasma that is increased in pregnancy and pregnancy-associated hypertension. The results of the present study demonstrate that the polymerization of AGT occurs through a novel mechanism which is primarily dependent on non-covalent linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…5D), respectively. Because the molecular mass was much higher than the theoretical mass of the complex, this suggests that these bands contain multimers of miropin that cannot be dissociated by boiling in SDS-PAGE sample buffer as observed previously for other serpins (34). Such dimers/trimers or higher multimers must contain a serpin molecule covalently attached to one end of the protease.…”
Section: Specificity Spectrum and Stoichiometry Of Inhibition Of Protmentioning
confidence: 92%
“…5D), respectively. Because the molecular mass was much higher than the theoretical mass of the complex, this suggests that these bands contain multimers of miropin that cannot be dissociated by boiling in SDS-PAGE sample buffer as observed previously for other serpins (34). Such dimers/trimers or higher multimers must contain a serpin molecule covalently attached to one end of the protease.…”
Section: Specificity Spectrum and Stoichiometry Of Inhibition Of Protmentioning
confidence: 92%
“…Likewise, the charge barrier in the GFB and the endothelial glycocalyx are also not likely to be responsible, because both AGT and albumin are negatively charged (more so in albumin). 24,26,27 Polymerization of the injected AGT 28 and/or binding to other plasma proteins could have caused lower glomerular permeability. However, electrophoresis of the infused solution and the animals' sera showed that the size of the majority of labeled proteins was around 60 kD (Supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the AGT molecule is known to be able to form disulfide-linked multimers, that are suggested to be the dominant constituent of the HMW fraction [16]. In addition, the presence of two different complexes containing proMBP (proform of eosinophil major basic protein) disulfide linked to AGT have been demonstrated [17,18].…”
Section: Introductionmentioning
confidence: 99%